2017
DOI: 10.1007/s12325-017-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Ibrutinib Versus Obinutuzumab + Chlorambucil in First-Line Treatment of Chronic Lymphocytic Leukemia: A Matching-Adjusted Indirect Comparison

Abstract: IntroductionIbrutinib (ibr) monotherapy and the combination of obinutuzumab plus chlorambucil (obi) are approved for previously untreated chronic lymphocytic leukemia (CLL). No trials directly comparing their efficacy are available. Therefore a matching-adjusted indirect comparison (MAIC) was performed to provide insight into their relative efficacy in terms of progression-free survival (PFS) and overall survival (OS). MAIC attempts to adjust for between-trial differences in factors known or suspected to influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…9 Our results confirm prior observations that ibrutinib appears to diminish the negative prognostic impact of del(11q) and unmutated IGHV observed with chemoimmunotherapy regimens. 10,11 Additionally, these results, which used patient-level data, are consistent with a recent cross-trial study that reported favorable PFS with single-agent ibrutinib (from REShaematologica 2020; 105:e166 ONATE-2) compared with published data from studies on first-line chemoimmunotherapy in CLL, 12,13 particularly for patients with del(11q) or unmutated IGHV. The median time to next treatment was not reached in either group (HR 0.115; 95% CI: 0.055-0.242; P<0.0001).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…9 Our results confirm prior observations that ibrutinib appears to diminish the negative prognostic impact of del(11q) and unmutated IGHV observed with chemoimmunotherapy regimens. 10,11 Additionally, these results, which used patient-level data, are consistent with a recent cross-trial study that reported favorable PFS with single-agent ibrutinib (from REShaematologica 2020; 105:e166 ONATE-2) compared with published data from studies on first-line chemoimmunotherapy in CLL, 12,13 particularly for patients with del(11q) or unmutated IGHV. The median time to next treatment was not reached in either group (HR 0.115; 95% CI: 0.055-0.242; P<0.0001).…”
supporting
confidence: 85%
“…Alessandra Tedeschi, 1 Richard Greil, 2 Fatih Demirkan, 3 Tadeusz Robak, 4 Carol Moreno, 5 Paul M. Barr, 6 Bertrand Anz, 7 David Simpson, 8 Gianluca Gaidano, 9 Osnat Bairey, 10 Don Stevens, 11 Devinder Gill, 12 Ian W. Flinn, 13 Thomas J. Kipps, 14 Jan A. Burger, 15 Jennifer Lin, 16 Thomas Webb, 17 Viktor Fedorov, 16…”
mentioning
confidence: 99%
“…These include patient age [6], fitness/comorbidities [7] and molecular cytogenetics [6,8]. Generally, for fit patients with advanced, symptomatic disease, the so-called 'full-dose fludarabine-based' regimen of fludarabine + cyclophosphamide + rituximab (FCR) is recommended [1].…”
Section: Aimmentioning
confidence: 99%
“…The MAIC methodology has been applied extensively in oncology to assess the effects of treatments for various tumor types. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…The MAIC methodology has been applied extensively in oncology to assess the effects of treatments for various tumor types. [11][12][13][14][15][16][17][18] The objective of this analysis was to evaluate the relative efficacy and safety of NIVOþIPI (index therapy) versus DABþTRAM, ENCOþBINI, and VEMþCOBI (comparators) in patients with BRAF-mutant advanced melanoma using MAICs. This analysis expands on a previously reported MAIC analysis that compared NIVOþIPI with DABþTRAM and VEMþCOBI in this patient population.…”
Section: Introductionmentioning
confidence: 99%